2022
DOI: 10.3390/md20110690
|View full text |Cite
|
Sign up to set email alerts
|

Thallusin Quantification in Marine Bacteria and Algae Cultures

Abstract: Thallusin, a highly biologically active, phytohormone-like and bacterial compound-inducing morphogenesis of the green tide-forming macroalga Ulva (Chlorophyta), was determined in bacteria and algae cultures. A sensitive and selective method was developed for quantification based on ultra-high-performance liquid chromatography coupled with electrospray ionization and a high-resolution mass spectrometer. Upon C18 solid phase extraction of the water samples, thallusin was derivatized with iodomethane to inhibit t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
(80 reference statements)
0
11
0
Order By: Relevance
“…However, ee determinations of polar compounds that form metal ion complexes may be problematic. To develop a reliable HPLC‐based method for ee determination of thallusin samples, we adapted our derivatization‐based workflow for thallusin analytics [49] . A first ee determination was undertaken with (−)‐thallusin samples taken from the synthesis described before.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ee determinations of polar compounds that form metal ion complexes may be problematic. To develop a reliable HPLC‐based method for ee determination of thallusin samples, we adapted our derivatization‐based workflow for thallusin analytics [49] . A first ee determination was undertaken with (−)‐thallusin samples taken from the synthesis described before.…”
Section: Resultsmentioning
confidence: 99%
“…To develop a reliable HPLC-based method for ee determination of thallusin samples, we adapted our derivatization-based workflow for thallusin analytics. [49] A first ee determination was undertaken with (À )-thallusin samples taken from the synthesis described before. After derivatization with iodomethane, the thallusin methyl ester enantiomers were separated on a chiral amylose column with a proper resolution factor (R = 2.6, Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, sulfonosphingolipid concentrations were below detection levels in rosette-inducing supernatant extracts supporting our hypothesis, that other yet unknown bacterial-derived metabolites might be the actual morphogens. A targeted MS-analysis of enriched and semi-purified fractions also revealed that neither sphingolipids, capnine bases, siderophores, nor the algae morphogen thallusin 26 were detectable within the active metabolite fractions leaving the chemical nature of the morphogen elusive.…”
Section: Resultsmentioning
confidence: 99%
“…To develop a reliable HPLC-based method for ee determination of thallusin samples, we employed our recently published derivatization-based workflow. [39] A first determination was undertaken with (-)-thallusin samples from the described synthesis. After methylation with iodomethane, the thallusin ester enantiomers were separated on a chiral amylose column with a proper resolution factor (R = 2.6, Fig.…”
Section: Resultsmentioning
confidence: 99%